Explorer - Matthews, Rupert; Stevenson, James, 1929- (New York : Knopf : Distributed by Random House, 1991)
Highlights various explorers and their discoveries.
Includes index.
Keywords: Discoveries in geography -- Juvenile literature; Explorers -- Juvenile literature; Discoveries in geography; Explorers